PENGARUH ALAT PERMAINAN EDUKATIF (PUZZLE) TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN DI DESA LINAWAN KECAMATAN PINOLOSIAN KABUPATEN BOLAANG MONGONDOW SELATAN - Muloke, Inggried Claudia; Ismanto, Amatus Yudi; Bataha, Yolanda (JURNAL KEPERAWATAN, 2017)
Abstrack: Preschoolers are children at aged 36-60 months, during this period a child is prepared for school, where the senses and stimuli as well as acceptance of the receptor and memory process should be ready so that a child is capable to study with well, the learning process at this time is with play. Children’s kognitive ability could be indicated with play a game that using educational tool game. The purpose of this research is known the influence of educational tool game (puzzle) on children’s cognitive development at aged 5-6 years in the village of Pinolosian Sub-district Linawan Bolaang Mongondow Regency South. The design of this research uses pre-experiment method with one group pretest-posttest design. Sampling techniques uses sampling size, at least about 30 respondents. The results of statistical tests on Paired Sample t-test with a confidence level of 95% (α = 0.05) and the obtained p value 0.000<0.05. The conclusion indicates that there is the influence of teducational tool game (puzzle) children’s cognitive development at aged 5-6 years in the village of Pinolosian Sub-district Linawan Bolaang Mongondow Regency South. Keywords : Educational tool game (puzzle), Cognitive Development, preschoolers Abstrak: Anak prasekolah adalah anak yang berumur 36-60 bulan, pada masa ini anak dipersiapkan untuk sekolah, dimana panca indra dan sistim reseptor penerimaan rangsangan serta proses memori harus sudah siap sehingga anak mampu belajar dengan baik, proses belajar pada masa ini adalah dengan cara bermain. Kemanpuan Kognitif anak dapat ditunjukan dengan cara melaksanakan kegiatan bermain menggunakan alat permainan yang mengandung unsur atau nilai edukatif. Tujuan Penelitian ini adalah diketahui pengaruh alat permainan edukatif (puzzle) terhadap perkembangan kognitif anak usia 5-6 tahun di desa Linawan Kecamatan Pinolosian Kabupaten Bolaang Mongondow Selatan. Desain Penelitian ini menggunakan metode Pra Eksperimen dengan pendekatan one group pretest-post test design. Teknik pengambilan Sampel menggunakan sampling size sebesar minimal 30 orang responden. Hasil Uji Statistik hasil uji Paired Sample t-test dengan tingkat kepercayaan 95% (α=0,05) dan diperoleh p value 0,000 < 0,05. Kesimpulan yaitu ada pengaruh alat permainan edukatif (puzzle) terhadap perkembangan kognitif anak usia 5-6 tahun di Desa Linawan Kecamatan Pinolosian Kabupaten Bolaang Mongondow Selatan. Kata Kunci : Alat Permainan Edukatif (Puzzle), Perkembangan Kognitif, Anak prasekolah